Case report: failure under azithromycin treatment in a case of bacteremia due to Salmonella enterica Paratyphi A - Kobayashi, Tetsuro (BMC Infect Dis, 2014)
BACKGROUND: Limited information is available regarding the clinical efficacy of azithromycin for the treatment of enteric fever due to fluoroquinolone-resistant Salmonella Typhi and Salmonella Paratyphi among travelers returning to their home countries. CASE PRESENTATION: We report a case of a 52-year-old Japanese man who returned from India, who developed a fever of 39°C with no accompanying symptoms 10 days after returning to Japan from a 1-month business trip to Delhi, India. His blood culture results were positive for Salmonella Paratyphi A. He was treated with 14 days of ceftriaxone, after which he remained afebrile for 18 days before his body temperature again rose to 39°C with no apparent symptoms. He was then empirically given 500 mg of azithromycin, but experienced clinical and microbiological failure of azithromycin treatment for enteric fever due to Salmonella Paratyphi A. However, the minimum inhibitory concentration (MIC) of azithromycin was not elevated (8 mg/L). He was again given ceftriaxone for 14 days with no signs of recurrence during the follow-up. CONCLUSION: There are limited data available for the treatment of enteric fever using azithromycin in travelers from developed countries who are not immune to the disease, and thus, careful follow-up is necessary. In our case, the low azithromycin dose might have contributed the treatment failure. Additional clinical data are needed to determine the rate of success, MIC, and contributing factors for success and/or failure of azithromycin treatment for both Salmonella Typhi and Salmonella Paratyphi infections.